Subjective Cash Flow and Discount Rate Expectations - DELAO, RICARDO; MYERS, SEAN (Journal of Finance, 2021)
ABSTRACT Why do stock prices vary? Using survey forecasts, we find that cash flow growth expectations explain most movements in the S&P 500 price‐dividend and price‐earnings ratios, accounting for at least 93% and 63% of their variation. These expectations comove strongly with price ratios, even when price ratios do not predict future cash flow growth. In comparison, return expectations have low volatility and small comovement with price ratios. Short‐term, rather than long‐term, expectations account for most price ratio variation. We propose an asset pricing model with beliefs about earnings growth reversal that accurately replicates these cash flow growth expectations and dynamics.